NCMP-08. CHALLENGING DIAGNOSIS AND MANAGEMENT OF PCNSL IN AN IMMUNOSUPPRESSED PATIENT ON MYCOPHENOLATE MOFETIL FOR MYASTHENIA GRAVIS. (12th November 2021) - Bricoune, Ornella; Mokhtari, Sepideh; Etame, Arnold; Robinson, Timothy; Pina, yolanda; Macaulay, Robert
Abstract: INTRODUCTION: Primary CNS lymphoma (PCNSL) typically presents with non-focal neurologic symptoms including disorientation, poor balance and memory and singel or multifocal periventricular MRI lesions. Deviations in characteristic findings can delay diagnosis and require additional diagnostic tests. OBSERVATION: A 68-year-old man with a recent zoster infection and acetylcholine receptor antibody positive myasthenia gravis (MG) on Mycophenolate Mofetil for 22 years presented at another institution with left eye vision changes, and focal neurological deficits. A brain MRI showed an enhancing lesion within his left medulla extending to the cerebellum. Cerebrospinal fluid (CSF) analysis was positive for EBV and negative for malignancy. He was diagnosed with VZV vasculopathy and discharged home on IV Acyclovir for 14 days and a 5-day course of oral prednisone 60 mg. Three months later, a repeat brain MRI showed multiple new enhancing lesions bilaterally along the periventricular white matter with involvement of the corpus callosum with several lesions in peripheral locations of the cerebrum, cerebellum, and brainstem. He presented to local ER with intermittent encephalopathy, acute left eye vision blurriness and was started on steroids. He was transferred to our institution and had CSF analysis which was positive for EBV and negative for malignancy. Due to rapid progression of his symptoms, he underwent gross total resection of the left frontal lesion which showed EBV-induced diffuse large B-cell lymphoma (DLBCL). His Mycophenolate Mofetil was discontinued and he had a dramatic improvement in his left eye vision and cognitive deficits within 24 hours after one dose of Rituximab IV 500 mg/m2. DISCUSSION: In the setting of periventricular lesions and EBV positivity on CSF, EBV-induced DLBCL should be highly considered. CONCLUSION: Misdiagnosis or delay in diagnosis of PCNSL due to the presence of atypical features in disease presentation and radiographic findings could lead to progression of PCNSL.